Leibniz, the Science and the Civil Code - Escobar Rozas, Freddy (2015)
Yhis article addresses the issue about the differences between the old regulatory bodies and the current Civil Codes. t he author analyzes from the Medieval Period until the present to evidence the change and evolution that made the thinkers to apply the geometric method to Law and how to configure the rules in the Civil Law. Furthermore, it recognizes and analyzes the contributions of e uropean writers and thinkers that promoted the Scientific Revolution of the 17th century, especially the work of the lawyer Gottfried Wilhelm Leibniz.